Old age pensions act, 1908. With notes together with the statutory regulations and official circulars issued by the Local Government Boards of England, Scotland, and Ireland, and financial instructions of the treasury. With an introd. by D. Lloyd George (Sweet & Maxwell, 1908)
With index.